Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Managing fisheries and ecosystems: current good practices and the EcoScope project experience - Georgi M. Daskalov; Santiago de la Puente; Marco Scotti; Stefania Klayn; Marie Briguglio; Gianpaolo Coro; Gideon Gal; Johanna J. Heymans; Ana Rodriguez-Perez; Jeroen Gerhard Steenbeek; Georgios Sylaios; Athanassios C. Tsikliras (Frontiers in Marine Science, 2025)
Ecosystem Based Management (EBM) is a comprehensive way of managing fisheries and marine resources. As such, it needs a large and complex suite of concepts and tools to address a variety of problems ranging from climate change, through various forms of water pollution, to trophic interactions and social-economic sustainability. Industry, scientists, managers, and policy makers involved in the fisheries sector are the main actors in EBM. EBM objectives based on policy needs, legal requirements, and ecosystem considerations may target specific fish stocks, or encompass several ecosystem components aiming for balanced fisheries, but they need to address the trade-offs between maximizing economic gains versus sustainable fisheries and healthy ecosystems. Fishing at Maximum Sustainable Yield (MSY), setting ecosystem reference points, discards ban, avoiding bycatch of protected species, habitat protection, accounting for the effects of climate change, achieving good environmental status, setting effective marine protected areas, and considering ecosystem effects from marine spatial planning, are all examples of EBM objectives. The EcoScope project aimed to address ecosystem degradation, anthropogenic impacts, and unsustainable fisheries by developing an efficient, holistic, ecosystem-based approach to sustainable fisheries management that can easily be used by policy makers and advisory bodies. The EcoScope consortium reflects an interdisciplinary advisory team of biologists, modelers, economists, and social scientists. It performed comprehensive reviews of data, data gaps, and various tools (models, indicators, management evaluation procedures). An online platform, toolbox, academy, and a mobile application are end products delivered and maintained by EcoScope to facilitate knowledge sharing, communication, and education. The EcoScope project has built modules ready to be used in the implementation of EBM, but a more direct approach by the responsible organizations, such as ICES, FAO, GFCM and the EC, is needed to set explicit and formal research and managerial frameworks for implementing and coordinating the EBM activities.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

Infection by the Marine Cestode Hepatoxylon trichiuri in Returning Chinook Salmon ( Oncorhynchus tshawytscha ) Spawners in Patagonia: Implications for a Novel Fishery - Guillermo Figueroa‐Muñoz; Patricio Torres; J. Marcos Rodriguez; Christina A. Murphy (Fisheries Management and Ecology, 2025)
Parasitological information may be useful for managing economically important fisheries by providing insights into population dynamics and health effects. The Chinook salmon ( Oncorhynchus tshawytscha ), an invasive species with high socio‐ecological importance in South America, supports recreational and incipient artisanal fisheries. In Southern Chile, the recent approval of coastal fisheries for returning Chinook salmon in some regions highlights the importance of understanding salmon foraging, habitat use, and commercial value. However, such information is lacking. Parasites have been extensively used as cost‐effective biological tags to identify fish stocks. We conducted the first parasitological examination of the marine tapeworm Hepatoxylon trichiuri larvae in returning adult Chinook salmon from the Cisnes River to assess its potential as a biological tag for returning Chinook salmon in Patagonia. Of 61 Chinook salmon from the Cisnes River, 52.46% were infected by H. trichiuri , with 1.65 ± 1.26 parasites per infected salmon (mean ± SD). Infection prevalence and intensity did not differ significantly between males and females. Infection intensity was higher in larger salmon but decreased with increasing salmon condition. Infection intensity was not significantly related to length, mass, or body condition. Infection prevalence and intensity of H. trichiuri varied spatially among Patagonian river‐basin populations of Chinook salmon, thereby supporting the use of H. trichiuri as a biological tag. Our findings provide important parasitological metrics that may enhance future management practices by informing geographic variability in foraging locations of adult salmon and their commercial value for human consumption.

Leveraging Remote Sensing and Theory to Predict Tree Size Abundance Distributions Across Space - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; J. Marcos Rodriguez; Ben Weinstein; David A. Orwig; Sydne Record (Global Ecology and Biogeography, 2025)
Background Remote sensing (RS) technologies provide unprecedented opportunities to assess forest structure at broad spatial scales. Light detection and ranging (LiDAR) is a powerful tool that offers detailed vertical information, but its consistent high‐resolution coverage can be limited across vast areas and quantifying understory vegetation remains challenging due to occlusion. Conversely, while high‐resolution RGB imagery is more accessible and valuable for large‐scale analyses, it comes with higher uncertainty and only captures canopy‐level information. Integrating RGB data with ecological theory and existing LiDAR‐derived products (e.g., canopy height models, CHM) allows us to enhance predictions and broaden the applicability of forest size structure mapping from the understory to the canopy, particularly through tree size–abundance relationships. Theory Tree size and abundance generally follow known distributions, where smaller trees are exponentially more common than larger trees. This pattern emerges from fundamental ecological constraints, including volume packing, metabolic scaling and light competition, which collectively govern forest self‐organisation across spatial scales. Proposed Approach We present a workflow that integrates size‐abundance scaling theory with RGB data and CHMs to improve predictions of forest structure. By estimating tree size distributions from RGB imagery, we extend the applicability of ecological scaling models to broader spatial scales and offer an approach that complements traditional methods. Assessment We apply this approach to forest monitoring networks, including NEON and ForestGEO, to assess its accuracy and generalisability across a range of forests (e.g., subtropical pine, boreal, low and dry, tall and dense) in North America. Our results show that RGB‐based estimates can successfully recover size‐abundance distributions from the understory to the canopy. Future Directions Further refinement of our approach could enhance predictions by incorporating species classifications from hyperspectral data and using more spatially or taxonomically specific allometric equations. These additions would enable more precise scaling of tree diameter from remote sensing data.

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

Exploring the potential of hydrolytic enzymes combined with antibacterial agents to disrupt pathogenic biofilms and disinfect released cells - Patricia Palafox-Rivera; Melvin R. Tapia-Rodriguez; Julio Cesar Lopez-Romero; Marco A. Lugo-Flores; Karen P. Quintero-Cabello; Brenda A. Silva-Espinoza; M. Reynaldo Cruz-Valenzuela; Filomena Nazzaro; J. Fernando Ayala-Zavala (Biofouling, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Sperm melatonin receptors, seminal plasma melatonin and semen freezability in goats - Alberto J. Cardenas-Padilla; Francisco Jimenez-Trejo; Marco Cerbon; Araceli Chavez-Garcia; Norma B. Cruz-Cano; Martin Martinez-Torres; Alicia Alcantar-Rodriguez; Alfredo Medrano (Theriogenology, 2024)

Welfare of rainbow trout at slaughter: Integrating behavioural, physiological, proteomic and quality indicators and testing a novel fast-chill stunning method - João L. Saraiva; Filippo Faccenda; María J. Cabrera-Álvarez; Michele Povinelli; Peter C. Hubbard; Marco Cerqueira; Ana Paula Farinha; Giulia Secci; Maria Vittoria Tignani; Lina F. Pulido Rodriguez; Giuliana Parisi (Aquaculture, 2024)

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Measurement of airborne nicotine, as a marker of secondhand smoke exposure, in homes with residents who smoke in 9 European countries - Elisabet Henderson; Luis A. Rodriguez Guerrero; Xavier Continente; Esteve Fernández; Olena Tigova; Nuria Cortés-Francisco; Sean Semple; Ruaraidh Dobson; Anna Tzortzi; Vergina K. Vyzikidou; Giuseppe Gorini; Gergana Geshanova; et al. (Environmental Research, 2023)

Correction: Amphibian phylogenetic diversity in the face of future climate change: not so good news for the Chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

Amphibian phylogenetic diversity in the face of future climate change: not so good news for the chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A robust machine learning framework to identify signatures for frailty: a nested case-control study in four aging European cohorts - David Gomez-Cabrero; Stefan Walter; Imad Abugessaisa; Rebeca Miñambres-Herraiz; Lucia Bernad Palomares; Lee Butcher; Jorge D. Erusalimsky; Francisco Jose Garcia-Garcia; José Carnicero; Timothy C. Hardman; Harald Mischak; Petra Zürbig; et al. (GeroScience, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Simulating rewetting events in intermittent rivers and ephemeral streams: A global analysis of leached nutrients and organic matter - Oleksandra Shumilova; Dominik Zak; Thibault Datry; Daniel von Schiller; Roland Corti; Arnaud Foulquier; Biel Obrador; Klement Tockner; Daniel C. Allan; Florian Altermatt; María Isabel Arce; Shai Arnon; et al. (Global Change Biology, 2019)
Climate change and human pressures are changing the global distribution and the extent of intermittent rivers and ephemeral streams (IRES), which comprise half of the global river network area. IRES are characterized by periods of flow cessation, during which channel substrates accumulate and undergo physico‐chemical changes (preconditioning), and periods of flow resumption, when these substrates are rewetted and release pulses of dissolved nutrients and organic matter (OM). However, there are no estimates of the amounts and quality of leached substances, nor is there information on the underlying environmental constraints operating at the global scale. We experimentally simulated, under standard laboratory conditions, rewetting of leaves, riverbed sediments, and epilithic biofilms collected during the dry phase across 205 IRES from five major climate zones. We determined the amounts and qualitative characteristics of the leached nutrients and OM, and estimated their areal fluxes from riverbeds. In addition, we evaluated the variance in leachate characteristics in relation to selected environmental variables and substrate characteristics. We found that sediments, due to their large quantities within riverbeds, contribute most to the overall flux of dissolved substances during rewetting events (56%–98%), and that flux rates distinctly differ among climate zones. Dissolved organic carbon, phenolics, and nitrate contributed most to the areal fluxes. The largest amounts of leached substances were found in the continental climate zone, coinciding with the lowest potential bioavailability of the leached OM. The opposite pattern was found in the arid zone. Environmental variables expected to be modified under climate change (i.e. potential evapotranspiration, aridity, dry period duration, land use) were correlated with the amount of leached substances, with the strongest relationship found for sediments. These results show that the role of IRES should be accounted for in global biogeochemical cycles, especially because prevalence of IRES will increase due to increasing severity of drying events.

Doubting dung: eDNA reveals high rates of misidentification in diverse European ungulate communities - Robert Spitzer; Marcin Churski; Annika Felton; Marco Heurich; Dries P. J. Kuijper; Marietjie Landman; Esther Rodriguez; Navinder J. Singh; Pierre Taberlet; Suzanne T. S. van Beeck Calkoen; Fredrik Widemo; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2019)

Characterisation of ground motion recording stations in the Groningen gas field - Rik Noorlandt; Pauline P. Kruiver; Marco P. E. de Kleine; Marios Karaoulis; Ger de Lange; Antonio Di Matteo; Julius von Ketelhodt; Elmer Ruigrok; Benjamin Edwards; Adrian Rodriguez-Marek; Julian J. Bommer; Jan van Elk; et al. (Journal of Seismology, 2018)

Association of physical activity with muscular strength and fat-free mass in adolescents: the HELENA study - Diego Moliner-Urdiales; Francisco B. Ortega; Germán Vicente-Rodriguez; Juan P. Rey-Lopez; Luis Gracia-Marco; Kurt Widhalm; Michael Sjöström; Luis A. Moreno; Manuel J. Castillo; Jonatan R. Ruiz (European Journal of Applied Physiology, 2010)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)